Highly efficient visible light induced photocatalytic activity of a novel in situ synthesized conjugated microporous poly(benzothiadiazole)–C3N4 composite. Issue 2 (21st December 2016) - Wang, Shengyao; Yang, Xianglong; Hou, Huijie; Ding, Xing; Li, Shenhui; Deng, Feng; Xiang, Yonggang; Chen, Hao
Abstract : Highly efficient visible light-driven heterojunction BBT–C3 N4 exhibits superior redox ability for sulfathiazole and Cr(vi ) removal. Abstract : In this study, a novel π-conjugated microporous poly(benzothiadiazole)–graphitic carbon nitride (BBT–C3 N4 ) photocatalyst was synthesized through a facile in situ palladium-catalyzed Sonogashira–Hagihara cross-coupling polycondensation of 4, 7-dibromobenzo[ c ][1, 2, 5]thiadiazole with 1, 3, 5-triethynylbenzene in the presence of evenly dispersed g-C3 N4 using mixed DMF/TEA as solvent at 80 °C. Systematic characterization results revealed that BBT was equally dispersed on the surface of C3 N4 with chemical bonds. The photocatalytic tests showed that this BBT–C3 N4 composite exhibited enhanced photocatalytic removal of both sulfathiazole and Cr(vi ) in comparison with the pure BBT and C3 N4 as well as a mechanical mixture of BBT and C3 N4, indicating that the oxidation and reduction abilities of BBT–C3 N4 were simultaneously enhanced after composition under visible light irradiation. This was subsequently confirmed by radical detection, PL analysis and scavenger experiments as well. Holes and photoelectrons were demonstrated to be the main active species during the photocatalytic removal of sulfathiazole and Cr(vi ), respectively. A possible photoelectron transfer mechanism for efficient photoinduced electron–hole separation of BBT–C3 N4 composites is proposed based on all the results. This study provides new insight into the design of highly efficient visible light-driven photocatalysts with superior redox ability for wastewater treatment.